Short-Term Results of Preterm Infants and Comparison with the Recent International Network: Obtained from a Level III Neonatal Intensive Care Unit in Türkiye - Yılmaz, Aslan; Kaya, Nesrin; Ünkar, Zeynep Alp; Ulu, Ersin; Sak, Kevser; Perk, Yıldız; Vural, Mehmet (Cerrahpaşa Medical Journal, 2024)
Objective: This study aimed to evaluate the effects of developments in neonatal units over time by comparing the results of the last 15 years of our unit with recent reliable international data. Methods: This study uses data from preterm infants and very-low-birth-weight infants enrolled in the Vermont Oxford Network (VON) system in a standard way. Our unit’s 15-year data (from 2005 to 2020) and VON data (for 2018) were compared in 3 subgroups of gestational age (<24 week, 24-26 week, and 27-29 week). Results: In the data of our unit, prenatal care (P = .019) and antenatal steroid administration (P < .001) were lesser than VON data, while the frequency of small for gestational age (P < .001), cesarean delivery (P = .001), and multiple pregnancies (P < .001) were higher. In our unit’s data, survival (P < .001) and morbidity-free survival (P < .001), respiratory distress syndrome (P = .008), surfactant treatment (P = .036), bronchopulmonary dysplasia (P < .001), discharge home with oxygen (P < .001), and nasal CPAP use before intubation at initial resuscitation (P < .001) were lesser than VON data. In the 15-year data of our unit, the frequency of severe intraventricular hemorrhage (P = .001) and nosocomial infection (P < .001) were found to be higher and patent ductus arteriosus (P < .001), and necrotizing enterocolitis (P = .022) were lower than VON 2018 data. Conclusion: As a result, we believe that neonatal intensive care unit (NICUs) need to store their data with a standard method and compare them with a database of a network to have a more critical view of the standards of health care that they provide. Cite this article as: Yılmaz A, Kaya N, Alp Ünkar Z, et al. Short-term results of preterm infants and comparison with the recent international network: Obtained from a level III neonatal intensive care unit in Türkiye. Cerrahpaşa Med J. 2024;48(1):40-45.